DEVELOPING A MODEL OF MOTHER’S EMPOWERMENT TO SUPPORT LEARNING AUTONOMY IN SAWOHAN VILLAGE - Mas'udi Dermawan; Siti Aisyah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to develop a mother-empowerment model to support children’s learning autonomy in Sawohan Village, Buduran District, Sidoarjo Regency. The program was motivated by the low level of parental involvement and limited understanding of effective home-learning strategies among mothers. A Participatory Action Research (PAR) approach was employed, involving mothers and community stakeholders in all stages of the program, including problem identification, planning, implementation, and evaluation. The activities consisted of community education, practical training, consultation and mentoring, and advocacy to ensure program sustainability.Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed using thematic qualitative analysis. The results indicate increased awareness among mothers regarding their roles in supporting children’s learning, improved practical skills in facilitating home-learning activities, and strengthened collaboration within the community. The program also produced simple handbooks and practical guidelines, as well as encouraged the formation of a community learning group (Kelompok Belajar Ibu dan Anak) as a local support network. Overall, the program resulted in a sustainable and replicable empowerment model that can be adapted in other communities with similar social and economic characteristics